2018
DOI: 10.1111/cch.12603
|View full text |Cite
|
Sign up to set email alerts
|

Father's and mother's beliefs about children's anxiety

Abstract: Background: Previous research has focused on parenting styles and parental behaviors associated with children's anxiety. Parental beliefs about their child's anxiety have scarcely been studied, in spite of their probable influence in parents seeking help. The present study intended to fil that gap, by exploring what parents think about their children's anxiety and whether these cognitions are related or not to their use of professional help. Method:In-depth semistructured interviews were conducted with 48 pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In the present study majority of parents were having a moderate level of negative belief about their child's experience of anxiety. These indings are in line with the observations done by (Beato et al, 2018), where Father' and mother's beliefs about children's anxiety were assessed. Findings revealed that most of the parents perceived the child's anxiety as a permanent condition, attributing it to external and parental factors and considering that the anxiety problems have a negative impact on the child's wellbeing.…”
Section: Data Presented In Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study majority of parents were having a moderate level of negative belief about their child's experience of anxiety. These indings are in line with the observations done by (Beato et al, 2018), where Father' and mother's beliefs about children's anxiety were assessed. Findings revealed that most of the parents perceived the child's anxiety as a permanent condition, attributing it to external and parental factors and considering that the anxiety problems have a negative impact on the child's wellbeing.…”
Section: Data Presented In Tablesupporting
confidence: 88%
“…It will help in minimizing the chances of the development of anxiety disorders in children, which is found to be prevalent all over the world. These indings also indicate that parent's negative beliefs about their child's experience of anxiety may affect their decision about seeking help from counsellors, which is detrimental for the emotional health of the child (Beato et al, 2018).…”
Section: Data Presented In Tablementioning
confidence: 94%
“…We found a stronger mismatch for anxiety and also bullying in children who visit therapists. This might be the case because parents may rely too heavily on the therapist and consider the issue solved-"Half of the parents who had sought professional help tended to believe in improvement in their child's anxiety" [47]-and, therefore, consider it gone. Also, therapy sessions give kids a place to safely express their feelings and deal with their anxieties, which may not be apparent to parents outside of therapy.…”
Section: Anxiety and Bullyingmentioning
confidence: 99%
“…It is commonly characterized as a condition of constant alertness accompanied by a constricted focus, a feeling of unease, overthinking concern, a perception of vulnerability, a restraint in actions, and an elevated level of sympathetic stimulation ( American Psychiatric Association, 2013 ). The potential long-term detrimental effects of untreated childhood anxiety on several aspects of a child development, including cognitive, social, and emotional functioning, tend to be more severe ( Barlow, 2002 ; Merikangas et al, 2009 ; Pereira et al, 2014 ; Beato et al, 2018 ). Therefore, determining the correlates of preschool children’s anxiety is extremely important in order to lessen their anxiety and encourage healthy adaption and growth.…”
Section: Introductionmentioning
confidence: 99%